Inclusive education pandemic: Learning barriers for children with disabilities in South Africa - Raymond Chirowamhangu (African Journal of Disability)
Background: Children with disabilities encounter obstacles attaining basic education. Significantly, previous studies on South Africa have shown that up to 70% of the children with disabilities are out of school. Despite efforts to support inclusive education through White Paper 6 policy, the deployment of resources and transformation of the education sector has been a slower process.